PROBLEMATIKA HISAB RUKYAH DALAM PENENTUAN AWAL RAMADHAN DAN SOLUSINYA DI INDONESIA - Imroatul Munfaridah (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Differences start of Ramadanis commonly happened. Still, there are concerns and doubts with this difference. The society is not fully aware ofthe source of the difference. People often require to unite thebeginning of Ramadan, at least in Indonesia or world wide. Some people simply argue, "With one month and sun, howcan the beginning of Ramadan and the eid el-fitrday be different?".Unfortunately, there is no necessityfor the society to follow the government decree. Theymay use methods other than those used by the government. Thus, there is a wide range of opinion on the initial start of the month. Because of those diversity will also affect the fasting it self.Therefore,a reviewof Fiqih in the old reference needs to be enriched further by incorporating advanced factors, including separated astronomical and scientific analysis. Ijtihadiyah problem continues to grow adding the diversity factor. From those, the author examines the problems of hisab rukyah in determining the start of Ramadan and its solution in Indonesia